Volcanic minerals in Chaco Canyon, New Mexico and their archaeological significance. (February 2018) - Tankersley, Kenneth Barnett; Huff, Warren D.; Dunning, Nicholas P.; Owen, Lewis A.; Scarborough, Vernon L.
Highlights: Ni, Cr, Pt anomaly and volcanic minerals documented in Chaco Canyon, New Mexico. AMS radiocarbon and OSL ages suggest that an ash fall occurred 1000–1150 CE. Sunset Crater, Arizona is the most likely source for the Pueblo II ash fall. Volcanic ash was important for Ancestral Puebloan ceramics and agriculture.